2004
DOI: 10.1152/ajplung.00385.2003
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosastimulates phosphorylation of the airway epithelial membrane glycoprotein Muc1 and activates MAP kinase

Abstract: We reported previously that Muc1 on the surface of epithelial cells was a receptor for Pseudomonas aeruginosa (Lillehoj EP, Kim BT, and Kim KC. Am J Physiol Lung Cell Mol Physiol 282: L751-L756, 2002). Other studies showed that the Muc1 cytoplasmic tail (CT) contains multiple phosphorylation sites, some of which are phosphorylated constitutively and associated with signaling proteins. However, the relationship between extracellular P. aeruginosa binding and intracellular signaling is unknown. To investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 44 publications
2
83
0
Order By: Relevance
“…7), we next asked whether NEU1 might regulate MUC1-dependent downstream signal transduction. In A549 cells or SAECs in which NEU1 was either silenced or overexpressed, flagellin-stimulated, MUC1-dependent ERK1/2 phosphorylation was studied as described previously (33). In MUC1-expressing ECs, P. aeruginosa-derived flagellin consistently increased ERK1/2 phosphorylation compared with the simultaneous medium control (Fig.…”
Section: Neu1mentioning
confidence: 69%
See 1 more Smart Citation
“…7), we next asked whether NEU1 might regulate MUC1-dependent downstream signal transduction. In A549 cells or SAECs in which NEU1 was either silenced or overexpressed, flagellin-stimulated, MUC1-dependent ERK1/2 phosphorylation was studied as described previously (33). In MUC1-expressing ECs, P. aeruginosa-derived flagellin consistently increased ERK1/2 phosphorylation compared with the simultaneous medium control (Fig.…”
Section: Neu1mentioning
confidence: 69%
“…ϭ 100). The cells were incubated for 30 min at 37°C with 10 ng/ml flagellin or medium alone and lysed, and the lysates were processed for phospho-ERK1/2 immunoblotting as described (33). The phospho-ERK1/2 blots were stripped and reprobed for total ERK2, and the phospho-ERK1/2 signal was normalized to total ERK2 signal in the same lane of the same gel.…”
Section: Rna Targetmentioning
confidence: 99%
“…6 These features enable cs-mucins to provide a barrier function to mucosal pathogens by displaying sites for pathogen binding, acting as a releasable decoy, and sterically blocking binding of pathogens to underlying cellular receptors. The cytoplasmic tail domain of cs-mucins is highly conserved across species, undergoes both serine and tyrosine phosphorylation, and interacts with kinases and adaptor molecules, [7][8][9][10][11] consistent with a role in signal transduction in response to pathogen binding. As IAV specifically binds sialic acid-expressing receptors to trigger its entry by endocytosis into epithelial cells, the virus also has the potential to interact with sialic acid on cs-mucins, which may modulate both the infection process and the host response.…”
Section: Introductionmentioning
confidence: 99%
“…MUC1 has been linked to the Ras-Raf-MEK-ERK cascade numerous times [14,[38][39][40]47], and at least two mechanisms by which MUC1 can alter MAPK signaling have been described: MUC1 interaction with and phosphorylation by the ErbB family [14,15], and MUC1 binding to the Grb2/Sos complex that activates Ras [47]. Reduction of MEK1 levels after MUC1 siRNA agrees with the role of MUC1 in strengthening MAPK signaling, and indicates that MUC1 can regulate both transcription and activity of members of this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, transcription of MAP2K1 was significantly decreased in both cell lines after MUC1 siRNA. This gene encodes MEK1, one of the primary regulators of the ERK1/2 MAPK pathway [37], a network which has been linked several times to MUC1 in cancer [14,[38][39][40]. We examined MEK1 and MEK2 levels by western blot to confirm decreased protein in MUC1 siRNA-treated cells, and found that not only were total MEK1/2 levels in 468.siMUC1 and BT.siMUC1 lower as compared to their respective controls, but so were the basal amounts of active (phosphorylated) MEK1/2 in BT.siMUC1 ( Figure 3, IB: MEK1/2 and IB: pMEK1/2).…”
Section: Transfection Of Sirna Oligonucleotides Transiently Decreasesmentioning
confidence: 99%